NUMERICAL INVESTIGATION ON THE PERFORMANCE OF THE PHOTO-THERMOELECTRIC AIR DUCT FOR BUILDINGS NIK - NIK ABDUL AZIZ, NIK AMIRUDDIN (2018)
Thermoelectric modules and photovoltaic panel is one of the renewable components installed in the building structure in order to regulate the conducive room temperature. Both thermoelectric module s and photovoltaic panel has been widely used in the building structure installation as it manages to provide the new medium in exploiting the natural energy without bring any harm towards the environmental condition. This study focuses on the improving the performance of the thermoelectric air duct systems design and configuration by modifying the existing design and configuration with respect of environment exhaust air to reduce the hot junction temperature of air duct. The problem arises when the coefficient of the performance and cooling capacity produces by the thermoelectric air duct systems is under the optimum conditions.